EVALUASI KAPASITAS PENAMPANG CHECK DAM I GUNUNG NAGO TERHADAP DEBIT BANJIR - sadtim sadtim; Wisafri Wisafri; Angga Putra Arlis; Ridho Wafiq Fauzan (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2026)
Padang City, the capital of West Sumatra Province, has complex topographical conditions that increase its susceptibility to flooding, particularly during periods of high rainfall intensity. One of the flood control infrastructures constructed along the Batang Kuranji River is Check Dam I Gunung Nago, which functions to reduce flood discharge and sediment transport. This study aims to evaluate the hydraulic capacity of the check dam cross-section in accommodating planned flood discharge under various return periods. The research methodology involved the collection and analysis of topographic, hydrological, and 15-year rainfall data obtained from the Gunung Nago and Ladang Padi rainfall stations. Design rainfall was analyzed using Normal, Gumbel, Log Normal, and Log Pearson Type III probability distributions, followed by goodness-of-fit tests employing the Chi-Square and Smirnov-Kolmogorov methods. Planned flood discharge was estimated using the Rational, Hasper, and Weduwen methods, as well as Snyder and Nakayasu synthetic unit hydrographs. The results indicate that the existing cross-section capacity of Check Dam I Gunung Nago is only capable of safely accommodating flood discharge with a return period of up to five years. Consequently, structural capacity enhancement and flood mitigation measures are necessary to improve the effectiveness of the check dam in flood management.